2011
DOI: 10.1016/j.ijlp.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

CIT in context: The impact of mental health resource availability and district saturation on call dispositions

Abstract: The goals of Crisis Intervention Team (CIT) programs include improving safety during encounters between police and persons with mental illnesses, diverting persons with mental illnesses away from the criminal justice system, and increasing referral and access to mental health services. CIT is a systemic intervention, and as such, its implementation and effectiveness are influenced by existing practices and infrastructures. However, little research has considered the context in which CIT programs are implemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…There is a suggestion that the severity of mental health problems was greater among diverted individuals that control group participants (Broner et al, ; Gratton et al, ), which may have constituted a barrier to sustained treatment over the longer term, so “increased oversight and more directive models of diversion” may help for such people (Lattimore, Broner, Sherman, Frisman, & Shafer, : 30). Other aspects that may influence outcomes include the availability of mental health services, timely linkage to treatment, and accurate mental health assessments (Bonkiewicz et al, ; Schwarzfeld, Reuland, & Plotkin, ; Watson, Ottati, Draine, & Morabito, ). The failure of diversion to result in sustained treatment for mental disorder, whatever the reason, may serve to explain the potential for adverse outcomes indicated by this review, for example, a finding that prearrest diversion was associated with an increased longer‐term risk of arrest (CIT, Portland; Broner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a suggestion that the severity of mental health problems was greater among diverted individuals that control group participants (Broner et al, ; Gratton et al, ), which may have constituted a barrier to sustained treatment over the longer term, so “increased oversight and more directive models of diversion” may help for such people (Lattimore, Broner, Sherman, Frisman, & Shafer, : 30). Other aspects that may influence outcomes include the availability of mental health services, timely linkage to treatment, and accurate mental health assessments (Bonkiewicz et al, ; Schwarzfeld, Reuland, & Plotkin, ; Watson, Ottati, Draine, & Morabito, ). The failure of diversion to result in sustained treatment for mental disorder, whatever the reason, may serve to explain the potential for adverse outcomes indicated by this review, for example, a finding that prearrest diversion was associated with an increased longer‐term risk of arrest (CIT, Portland; Broner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Using data from researcher‐administered surveys of Chicago police officers about mental‐health‐related calls they had responded to in the prior month, Watson and colleagues (, ) found that CIT officers linked a greater proportion (effect size d = .49) of individuals to psychiatric care (transport to a hospital or other referral) and were less likely to provide no intervention than their non‐CIT peers ( d = .25). There was no difference found in arrests.…”
Section: What Evidence Is There To Date?mentioning
confidence: 96%
“…Faced with what Punch also described as the “gray area” of “secret social service” work (1979, p. 102), officers function as “peacekeepers” (Banton, 1964; Bittner, 1967a, 1967b, 1970b, 1990; Reiner, 2015), handling matters without invoking the law or using the civil commitment system (Watson, Ottati, Draine, & Morabito, 2011; Watson et al, 2010). In this light, current research and policy efforts may overlook the vast array of lower intensity and less formal interactions and their potential not only to prevent future arrest or transport situations, but also to establish trust and build positive rapport that may pay forward to subsequent interactions.…”
Section: Introductionmentioning
confidence: 99%